James McCauley Landis papers - Landis, James McCauley, 1899-1964.; Brown, Dorothy Purdy, 1908-2010.
Correspondence, memoranda, interviews, writings, legal drafts and briefs, financial records, scrapbooks, photographs, and other papers relating to Landis's career as professor of law and dean of the Harvard Law School, chairman of the U.S. Securities and Exchange Commission, chairman of the U.S. Civil Aeronautics Board, director of economic operations and minister to the Middle East during World War II, advisor to President John F. Kennedy, and supervisor for the town of Harrison, N.Y. Subjects include the controversy over the plan to reorganize the U.S. Supreme Court in 1936, the Harry Bridges legal case, presidential election of 1940, public administration, the U.S. Federal Power Commission, and the motion picture and televison industry. Includes material pertaining to Landis's law practice, New York, N.Y.; papers of Landis's second wife, Dorothy Purdy Brown; and material gathered by Donald A. Ritchie for his biography of Landis.
Correspondents include Louis Dembitz Brandeis, Benjamin N. Cardozo, Zechariah Chafee, William O. Douglas, Felix Frankfurter, John F. Kennedy, Joseph P. Kennedy, David Eli Lilienthal, Langdon P. Marvin, Claude Pepper, Roscoe Pound, Richard Manning Russell, and Herbert Bayard Swope.
Library of Congress Prints and Photographs Division.
Government official, lawyer, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Bridges, Harry, -- 1901-1990 -- Trials, litigation, etc; Cardozo, Benjamin N. -- 1870-1938 -- Correspondence; Chafee, Zechariah, -- 1885-1957 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963 -- Correspondence; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Lilienthal, David Eli, -- 1899-1981 -- Correspondence; Marvin, Langdon P. -- 1876-1957 -- Correspondence; Pepper, Claude, -- 1900-1989 -- Correspondence; Ritchie, Donald A., -- 1945-; Pound, Roscoe, -- 1870-1964 -- Correspondence; Russell, Richard Manning, -- 1891- -- Correspondence; Swope, Herbert Bayard, -- 1882-1958 -- Correspondence; United States. -- Civil Aeronautics Board; United States. -- Federal Power Commission; United States. -- Securities and Exchange Commission; United States. -- Supreme Court; Harvard Law School; Aeronautics, Commercial; Economic development -- Middle East; Law -- Study and teaching -- United States; Motion picture industry; Practice of law -- New York (State) -- New York; Public administration; Securities -- United States; Television broadcasting; World War, 1939-1945 -- Middle East; Harrison (N.Y.) -- Politics and government; Middle East -- Economic conditions; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Middle East; Educators; Lawyers; Public officials